2014
DOI: 10.2217/fon.13.187
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Solubilized Vemurafenib Administered via Nasogastric Tube

Abstract: Until only a few years ago, there was only one truly effective therapy for patients with metastatic melanoma. While long-term remission could be achieved in some patients, toxicities associated with high-dose IL-2 were significant. New insight related to molecular pathways of tumor cells indicated that an activating mutation of BRAF can be found in approximately 50-60% of all patients with melanoma. Proof-of-concept demonstrated in clinical trials of a drug targeting mutant BRAF led to the approval of vemurafe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
(4 reference statements)
0
4
1
Order By: Relevance
“…In both cases, patients had a partial response and a significant benefit of short duration. 6,7 Compared to our patients, there was no difference in efficacy and tolerance of this altered administration of treatment. Even if the efficacy of treatment was short-lived, patients and family appreciated our having tried to provide the best care.…”
Section: Discussioncontrasting
confidence: 66%
“…In both cases, patients had a partial response and a significant benefit of short duration. 6,7 Compared to our patients, there was no difference in efficacy and tolerance of this altered administration of treatment. Even if the efficacy of treatment was short-lived, patients and family appreciated our having tried to provide the best care.…”
Section: Discussioncontrasting
confidence: 66%
“…A further illustration of alternate delivery methods involving the dispersal of vemurafenib has been published. 14 The technique described involves dissolving each vemurafenib capsule in 15 mL of water before administering it via nasogastric tube or feeding tube and then flushing the tube with 30 mL of water per capsule. The technique described would not have been applicable here as the capsule formulation is not available in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Review of agents found 36 (31%) with guidance for alternative routes of administration readily available in tertiary resources or commercial liquid formulations, 38 (33%) with off‐label manufacturer information or case reports describing manipulation of solid dosage formulations, and 42 (36%) with no data or insight limited to pharmacokinetic studies. Findings are detailed in Table 3 10‐196 . Unique administration instructions (ie, with or without foo...…”
Section: Resultsmentioning
confidence: 99%